Pemeliharaan upacara sogit perkahwinan masyarakat Dusun di Ranau Sabah dalam situasi yang berubah - Veronica, Adam. (Universiti Malaysia Sarawak (UNIMAS), 2012)
Sogit in wedding ceremony is an old heritage of traditional ethnic Dusun in Ranau, Sabah. This study was conducted to study the preservation of sogit in marriage Ceremony by the Dusun community in a changing situation. The case study is conducted in the village of Toboh Lama, Ranau. Through this study, the difference in the performance of sogit in marriage ceremonies during Toboh Lama villagers still adopt animist religion and when they embrace Islam and Christianity region will be identified. The role of various parties such as members of village committees, bodies of arts and culture as well as Dusun community to be considered in order to maintain the tradition sogit also highlighted in this study. The findings are important as a source of reference on sogit preservation of marriage in society, especially the young orchard.